Globalization and Islamic Indigenization in Southeast Asian Muslim Communities - James Hoesterey (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2022)
For centuries, what is now commonly referred to in the Cold War-inflected English parlance as “Southeast Asia” has been connected to various regions of the world – from the transmission of Islam from diverse places in the Middle East, South Asia, and China, to engagements with European colonialism and, more recently, post-independence foreign relations in various regional, multilateral, and global contexts. From the eighth century Muslim traders were traversing the ports of what is now called Southeast Asia, and by the turn of the fourteenth century there is evidence for indigenous Muslim communities.[1] Such economic, cultural, and religious exchange over the centuries has not, despite the warnings of some globalization theorists, led to a homogenization of Southeast Asia, much less a homogenization of Islamic ideas and practices. Rather than coming as a single homogenous and authoritative source, the spread of Islam – and Muslim leaders – across mainland and island Southeast Asia came from many directions and influences from Mecca and Medina to the Swahili Coast, Yemen, India, the Persian Gulf, Patani networks, and as far as China. Whereas some transmission of Islamic ideas from the Middle East (often led by Southeast Asians, or Jawi, pilgrims, scholars, and travelers who return home) have led to contentious debates and power struggles in particular moments and places, such as the struggle between “old” and “young” movements among Minangkabau in West Sumatra, more recently Southeast Asia – especially Muslim Southeast Asia – has experienced other forms of cultural influence and exchange with East Asian countries like Japan and Korea as well as Western countries from the United States to former European colonial powers.[2] As a nation-state, Indonesia has also begun to come to terms with Chinese Muslims as part of the long histories of Islam and Muslims in the archipelago. Along the way, Southeast Asia’s ethnic communities have retained a sense of cultural, national, and religious identities that are influenced, yet never entirely determined, by outside forces. [1] Feener 2019, “Islam in Southeast Asia to c. 1800,” Oxford Research Encyclopedia. https://doi.org/10.1093/acrefore/9780190277727.013.40 [2] For Malaysia, see Michael G. Peletz, Sharia Transformations: Cultural Politics and the Rebranding of an Islamic Judiciary (Berkeley: University of California Press, 2020). For the influence of K-Pop, see Ariel Heryanto, Identity and Pleasure: The Politics of Indonesian Screen Culture (Singapore: NUS Press, 2014).